Genotypic Variation of Seed Oil Content in Twelve Genotypes of Citrullus colocynthis from Morocco - Madidi*, Saïd El; Benmoumou, Abedlhamid (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Citrullus colocynthis (L.) Schrad (2n = 22) is a perennial herbaceous species of the family Cucurbitaceae. It has natural tolerance to drought with a deep root system and is widespread in the arid and semi-arid zones of Africa and the Mediterranean region. This plant can be considered as a new potential source of vegetable oil. Twelve accessions of C. Colocynthis, collected from different regions of Morocco, were studied for seed and oil yields. The average yields obtained under non-optimal growing conditions are 479 kg/ha for seed yield and 99 kg/ha for oil yield. Significant genotypic variability was observed for seed oil content, seeds yields and oil yields. Heritability and genotypic advance are moderate to high for the characters measured. The exploitation of this variability could be used for the selection of accessions that have good oil yields in limited growing conditions. Keywords: Citrullus colocynthis; seeds yield; oil yield; oil content; oil composition *Corresponding author: Tel.: (+212) 528220957 Fax: (+212) 528220100 E-mail: s.elmadidi@uiz.ac.ma